2022
DOI: 10.1093/jnci/djac164
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Hazard Evaluations for Contemporary Needs: Highlights From New National Toxicology Program Evaluations and Methodological Advancements

Abstract: The National Toxicology Program (NTP) strives to raise awareness of cancer hazards in our environment. Identifying cancer hazards is key to primary prevention, informing public health decision-making, and decreasing the global cancer burden. In December 2021, the U.S. congressionally mandated 15th Report on Carcinogens (RoC) was released, adding eight new substances to the cumulative report. Chronic infection with Helicobacter pylori is listed as ‘known to be a human carcinogen’. Antimony trioxide and six halo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The results confirmed that the amount of residual monomers (< 0.2%) remained within the FDA safety limits (fig. S9) ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results confirmed that the amount of residual monomers (< 0.2%) remained within the FDA safety limits (fig. S9) ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the 15th edition of the carcinogen report in the United States, 97 , 98 H. pylori infection is a global health concern and a known carcinogen. In addition, according to the H. pylori Taipei Global Consensus, the majority of gastric cancers can be avoided if H. pylori infection is eradicated from the population.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Instead, the lung cancer tissue microbiome is less varied than the corresponding normal tissue microbiome ( Peters et al, 2019 ). In reality, only one specific bacterial species, Helicobacter pylori , which is linked to gastric cancer designated by the World Health Organization as a class I carcinogen ( Lunn et al, 2022 ), and research into other bacterial species’ potential roles as biomarkers in the majority of cancer types has not yet produced any conclusive findings ( Scott et al, 2019 ). There is a large variety of microbial taxa with variable abundance but little overlap in studies of males with prostate cancer ( Shrestha et al, 2018 ).…”
Section: Bacterial Diversity In Different Cancersmentioning
confidence: 99%